Environmental cold exposure increases blood flow and affects pain sensitivity in the knee joints of CFA-induced arthritic mice in a TRPA1-dependent manner. Issue 1 (December 2016) - Fernandes, Elizabeth; Russell, Fiona; Alawi, Khadija; Sand, Claire; Liang, Lihuan; Salamon, Robin; Bodkin, Jennifer; Aubdool, Aisah; Arno, Matthew; Gentry, Clive; Smillie, Sarah-Jane; Bevan, Stuart; et al.
Abstract Background The effect of cold temperature on arthritis symptoms is unclear. The aim of this study was to investigate how environmental cold affects pain and blood flow in mono-arthritic mice, and examine a role for transient receptor potential ankyrin 1 (TRPA1), a ligand-gated cation channel that can act as a cold sensor. Methods Mono-arthritis was induced by unilateral intra-articular injection of complete Freund's adjuvant (CFA) in CD1 mice, and in mice either lacking TRPA1 (TRPA1 KO) or respective wildtypes (WT). Two weeks later, nociception and joint blood flow were measured following exposure to 10 °C (1 h) or room temperature (RT). Primary mechanical hyperalgesia in the knee was measured by pressure application apparatus; secondary mechanical hyperalgesia by automated von Frey system; thermal hyperalgesia by Hargreaves technique, and weight bearing by the incapacitance test. Joint blood flow was recorded by full-field laser perfusion imager (FLPI) and using clearance of99m Technetium. Blood flow was assessed after pretreatment with antagonists of either TRPA1 (HC-030031), substance P neurokinin 1 (NK1 ) receptors (SR140333) or calcitonin gene-related peptide (CGRP) (CGRP8–37 ). TRPA1, TAC-1 and CGRP mRNA levels were examined in dorsal root ganglia, synovial membrane and patellar cartilage samples. Results Cold exposure caused bilateral primary mechanical hyperalgesia 2 weeks after CFA injection, in a TRPA1-dependent manner. In animals maintained at RT, clearance techniques and FLPI showed that CFA-treated joints exhibited lower blood flow than saline-treated joints. In cold-exposed animals, this reduction in blood flow disappears, and increased blood flow in the CFA-treated joint is observed using FLPI. Cold-induced increased blood flow in CFA-treated joints was blocked by HC-030031 and not observed in TRPA1 KOs. Cold exposure increased TRPA1 mRNA levels in patellar cartilage, whilst reducing it in synovial membranes from CFA-treated joints. Conclusions We provide evidence that environmental cold exposure enhances pain and increases blood flow in a mono-arthritis model. These changes are dependent on TRPA1. Thus, TRPA1 may act locally within the joint to influence blood flow via sensory nerves, in addition to its established nociceptive actions.